Numerical simulation of plasticity in double lap metallic bolted joints - Grasso, Marzio; Bai, Yuanli; Brighton, James; Carless, Owen; St Leger-Harris, Chris (Taylor & Francis, 2023)
This article aims to compare three plasticity models, namely Bai-Wierzbicki (BW), von Mises and Drucker Prager, to predict the failure modes in double-lap metallic bolted joints under shear loading. The double-lap bolted joint finite element model has been validated against literature data, which demonstrated the application of BW ductile fracture model to bolt joint failure prediction. Taguchi Design is used to investigate the effects of geometrical parameters, preload and stress triaxiality on the failure modes. Force–displacement response amongst the three models differs up to 20% when failing in shear and a different prediction of the failure mode (shear out vs. net section) under the same loading and geometry conditions is observed.
Keywords: FEA; double-lap bolted joint; ductile fracture; damage modeling; Bai-Wierzbicki (BW); von Mises; Drucker Prager